AN UNUSUAL FORM OF SILICOSIS IN A STONE-CUTTER - S. A. Sharifian; A. H. Mehrparvar S. Mohammadi (Acta Medica Iranica, 2007)
Silicon dioxide or silica is the earth’s most abundant mineral. The primary pulmonary illness attributable to silica exposure is silicosis, which is observed in three forms: classic, accelerated and acute. A case of silicosis is presented in this article who has been working in a stone-cutting plant. He had suffered from symptoms of silicosis one year after employment in this plant (acute form), but his radiologic findings were compatible with accelerated or chronic silicosis. One of the important occupational diseases is silicosis, which is not treatable but is preventable. However, because of lack of appropriate engineering controls or personal protective devices in some workplaces we observe cases of silicosis yet.